Data from: Long-lived rodents reveal signatures of positive selection in genes associated with lifespan - Sahm, Arne; Bens, Martin; Szafranski, Karol; Holtze, Susanne; Groth, Marco; Görlach, Matthias; Calkhoven, Cornelis; Müller, Christine; Schwab, Matthias; Kraus, Johann; Kestler, Hans Armin; Cellerino, Alessandro; et al. (Dryad, 2019)
The genetics of lifespan determination is poorly understood. Most research
has been done on short-lived animals and it is unclear if these insights
can be transferred to long-lived mammals like humans. Some African
mole-rats (Bathyergidae) have life expectancies that are multiple times
higher than similar sized and phylogenetically closely related rodents. To
gain new insights into genetic mechanisms determining mammalian lifespans,
we obtained genomic and transcriptomic data from 17 rodent species and
scanned eleven evolutionary branches associated with the evolution of
enhanced longevity for positively selected genes (PSGs). Indicating
relevance for aging, the set of 250 identified PSGs showed in liver of
long-lived naked mole-rats and short-lived rats an expression pattern that
fits the antagonistic pleiotropy theory of aging. Moreover, we found the
PSGs to be enriched for genes known to be related to aging. Among these
enrichments were “cellular respiration” and “metal ion homeostasis”, as
well as functional terms associated with processes regulated by the mTOR
pathway: translation, autophagy and inflammation. Remarkably, among PSGs
are RHEB, a regulator of mTOR, and IGF1, both central components of
aging-relevant pathways, as well as genes yet unknown to be
aging-associated but representing convincing functional candidates, e.g.
RHEBL1, AMHR2, PSMG1 and AGER. Exemplary protein homology modeling
suggests functional consequences for amino acid changes under positive
selection. Therefore, we conclude that our results provide a meaningful
resource for follow-up studies to mechanistically link identified genes
and amino acids under positive selection to aging and lifespan
determination.
Alignments and positively selected sitesThe package contains
visualizations of alignments and positively selected sites for all genes
and branches that were analyzed in the corresponding
article.supplement_data.tar.gz
Keywords: Bathyergidae; AMHR2; Spalax; thioredoxin; positive selection; transferrin; Expression changes during aging; Naked mole-rat; IGF1; TXN; SOD2; AGER; MTOR; Evolution of longevity; TF; RHEB; Superoxide dismutase; Blind mole rat; PSMG1; heterocephalus glaber; RHEBL1; African mole-rats; Antagonistic pleiotropy